2021
DOI: 10.1242/jcs.254870
|View full text |Cite
|
Sign up to set email alerts
|

Dynein light intermediate chains as pivotal determinants of dynein multifunctionality

Abstract: In animal cells, a single cytoplasmic dynein motor mediates microtubule minus-end-directed transport, counterbalancing dozens of plus-end-directed kinesins. The remarkable ability of dynein to interact with a diverse cargo spectrum stems from its tightly regulated recruitment of cargo-specific adaptor proteins, which engage the dynactin complex to make a tripartite processive motor. Adaptor binding is governed by the homologous dynein light intermediate chain subunits LIC1 (DYNC1LI1) and LIC2 (DYNC1LI2), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 99 publications
(170 reference statements)
1
14
0
Order By: Relevance
“…Other isoform-specific roles for LICs have been described (see introduction), particularly in mitosis, where it has been proposed that LIC phosphorylation, coupled with Pin1 binding, may help control which adaptors bind to LIC1 and LIC2 during mitosis (Kumari et al, 2021a; Kumari et al, 2021b). LIC phosphorylation, notably in the region just upstream of helix 1, also plays a key role in switching dynein from interphase to mitotic cargos (Addinall et al, 2001; Dwivedi et al, 2019; Kumari et al, 2021a; Niclas et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other isoform-specific roles for LICs have been described (see introduction), particularly in mitosis, where it has been proposed that LIC phosphorylation, coupled with Pin1 binding, may help control which adaptors bind to LIC1 and LIC2 during mitosis (Kumari et al, 2021a; Kumari et al, 2021b). LIC phosphorylation, notably in the region just upstream of helix 1, also plays a key role in switching dynein from interphase to mitotic cargos (Addinall et al, 2001; Dwivedi et al, 2019; Kumari et al, 2021a; Niclas et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The LICs have an unstructured carboxy terminus which protrudes from the motor complex (Celestino et al, 2019; Lee et al, 2018; Schroeder et al, 2014). While the GTPase-like domain sequence is highly conserved between LIC1 and 2, there is less homology in the C terminus apart from two regions of predicted alpha-helix (Celestino et al, 2019; Kumari et al, 2021b; Lee et al, 2020; Lee et al, 2018). As described below, this C-terminal domain mediates the interaction between dynein and the recently identified activating cargo adaptors.…”
Section: Introductionmentioning
confidence: 99%
“…LIC1-CTD exhibits the architecture of an intrinsically disordered protein region, characterized by helical binding motifs H1 and H2 and flanked by flexible, unstructured linkers L1 and L2 ( Kumari et al, 2021 ). Nuclear magnetic resonance studies have revealed multiple points of contact with adaptors in LIC1-CTD, primarily in H1 (440–455), H2 (493–502), and linker L1 (418–421; Celestino et al, 2019 ), although H1 is the minimum indispensable binding motif ( Lee et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the short span of mitosis, dynein subpopulations could be required to dynamically switch between diverse functions, necessitating the rapid and finely tuned association with a diverse set of adaptors, cofactors, and cargoes, which could be dictated by conformational modulation of the LIC1-CTD. Interestingly, there are also several non-cdk1 mitotic phosphosites in the LIC1-CTD ( Dephoure et al, 2008 ; Olsen et al, 2010 ), which, in combination with the cdk1 sites, could exponentially increase the potential number of unique phosphorylated permutations to finely regulate the interactions and functions of mitotic dynein ( Kumari et al, 2021 ). Interestingly, the hydrophobic adaptor NTD clefts that interact directly with the hydrophobic H1 of LIC1-CTD are positioned in close proximity to several conserved negatively charged residues (present in all three classes of adaptors; Lee et al, 2020 ; Schroeder and Vale, 2016 ) and could therefore be electrostatically repelled due to LIC1-CTD phosphorylation around the points of contact with the adaptor, possibly inhibiting the binding of specific adaptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation